Pelaksanaan Monitoring Kepala Sekolah dalam Kegiatan Pembelajaran di Sekolah Sasnasuksa Sayap Provinsi Selatan Thailand Tahun 2015-2016 - Pohsu, Mr. Ahamah; , Drs, M. Yusron, M.Ag (2016)
The main activity of education in schools in order to realize the goal is learning activities, so that all activities of the school organization is oriented to the achievement of the efficiency and effectiveness of the school. Not just the principal control and the teachers conduct, but also to equip themselves with knowledge and understanding of the duties and functions of his staff, in order to make the supervision and control work well and not confuse. The principal monitoring to school teachers in learning activities of Sasnasuksa (Sayap) is an effort to find solutions to the problems of the principal monitoring. Then the results of this study can be made as one of the considerations to critic and evaluate principals. The research having done is a kind of field research with using descriptive qualitative approach, After the data is collected by the methods then analyzed qualitatively of observation, interview, and documentation, Subjects in this study are the principals of Sasnasuksa (Sayap) school, and a teacher who teaches 80 students. While the object is the principal task of monitoring the activities of teacher instruction in Sasnasuksa (Sayap) school. Monitoring of learning activities by the principal of Sasnasuksa (Sayap) is very well done. In the monitoring of learning activities,the principal controls through many aspects, namely: (1)Method of Learning, Where in the school principal provides suggestions and feedback regarding teaching methods. Later, the teacher seeks a range of methods and implement them. (2) Classroom Management, in Sasnasuksa (Sayap) school, classroom management, is done through lesson planning prepared a week earlier. Some, make statements after the teaching is over. (3) The class curriculum, monitoring is done in this aspect through research report created by a class act teacher. With the researchproduced by the teachers, the principal is able to provide an assessment of the teachers related to ideal classroom curriculum design. But this is less does not work well as some teachers do not prepare the research report (4)Evaluation Process Monitoring, which is done by direct monitoring in the classroom learning process between teachers and students. Keywords: Principal, Monitoring, Perception Teachers